Effects of Ethanol: Water Ratio and Reaction Time on Ethyl Levulinate Synthesis from Oil Palm Empty Fruit Bunch (OPEFB) - Widjaja Christopher; Heriyanti; Namhaed Kritsana; Gozan Misri (E3S Web of Conferences, 2024)
World energy consumption continues to escalate annually in line with current world development. Meeting this burgeoning demand necessitates the exploration of renewable energy. Biofuel is one of the promising alternatives for renewable energy sources. However, biofuel has a disadvantage in its lower overall performance than fossil fuel. The application of additives such as ethyl levulinate emerges as a potential solution to enhance biofuel performance. This research aims to investigate the effect of ethanol:water ratio and reaction time on the formation of ethyl levulinate from Oil Palm Empty Fruit Bunch (OPEFB). The OPEFB to be utilized was pretreated with 3% NaOH at a solid-to-liquid ratio of 1:8. The reaction was conducted at 120oC, with varying ethanol:water ratio and reaction time in the presence of H2SO4 as the catalyst. The reaction products were extracted using ethanol and analyzed with gas chromatography–mass spectrometry. The optimum reaction conditions obtained were 90 minutes and ethanol:water ratio of 99.1:0.9, resulting in a yield of 1.01%.